INOVASI LITERASI DIGITAL PENDEKATAN BARU DALAM KEGIATAN PENGABDIAN UNTUK MERESPONS TANTANGAN DIGITAL - Permana, Sulwan; Muhammad Ali Faishal; Muhammad Ridho; Moch. Galdiaz Nugraha Prawira; Nurcinta Asih; Muthia Mutmainah Aprinelia; Fahril Sidik Alfarizi; M.Miskun Arrihussalam; Ryan Ardiansyah; Rizki Anugrah Munawar; Sifa Nur Maisah; Dadang Permana; Sandi Dzulfikar; Rahma Rohimah Hinaffisah; Nazwa Tiara Herdiani; Ahmad Tavip Baiturahman; Rohimat; Anzilal Fauji; Muhammad Suryadindin; Lindawati (Jurnal PkM MIFTEK, 2023)
In an increasingly digitally connected era, digital literacy is an essential key skill for participating in an increasingly connected global society. Limitations in digital literacy can result in inequalities in access to information and opportunities, isolating some communities from the benefits offered by the digital world. Salakuray Village, like many other villages, faces challenges in keeping up with rapid changes in digital technology. The aim of this activity is to introduce an innovative approach to digital literacy implemented in Salakuray Village. This activity uses the door to door method and digital literacy seminars to provide the public with an understanding of digital literacy. The results show increased participation, especially of women, in the digital world. In addition, digitally literate people are starting to become active online, with some even starting their own online businesses. This service activity highlights the importance of continuing to encourage digital literacy efforts at the local level and provides valuable insight into how innovations in digital literacy can be implemented in various communities around the world.